AKTUALISASI SILA PERTAMA PANCASILA PADA PEMBELAJARAN DI SEKOLAH DASAR SEBAGAI PENINGKATAN KARAKTER RELIGIUS - Pane, Syafitria Rahma; Muhammad Nurwahidin,; Sudjarwo, Sudjarwo (Journal of Innovation Research and Knowledge, 2022)
Religious character is the most basic and main character that needs to be instilled in learners because religion becomes the basis in the life of the individual, society, and the State. The data collected by the author is a journal article with a range of 2018 to 2022. This data is determined by the systematic literature review method. The source of the literature review is obtained from search results on the Google Schoolar electronic database. In the first precept reads" Almighty Godhead" there are religious values including: a) Belief in the existence of an Almighty God with his all-perfect qualities, and b) Devotion to God Almighty, that is, to abide by all of his rules and obey all of his commands.